Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

$$2x-\dfrac{x+1}{2} + \dfrac{1}{3}(x+3)= \dfrac{7}{3}$$

When I solve this I always end up with 11x = 5, which is wrong, no matter which way I solve it. Does anyone know how to solve it? Steps? (Because I know the answer should be x=1)

share|improve this question
    
uhm -- is this $(1/3) (x+3)$ or $\frac{1}{3(x+3)}$ –  user20266 Dec 12 '11 at 18:35
    
Added a picture –  Friend of Kim Dec 12 '11 at 18:38
    
I removed the picture after clearing up the equation. –  The Chaz 2.0 Dec 12 '11 at 18:45
    
You do not show your work, so I am guessing. But when we bring the left side to the common denominator $6$, we get $\frac{12x-3(x+1)+2(x+3)}{6}$. The top simplifies to $11x+3$. You probably simplified it wrongly to $11x+9$. Minus signs are evil. –  André Nicolas Dec 12 '11 at 18:46
    
I know, they are! I didn't realize that it was one term, so it got -3 instead of +3. Thanks everyone! –  Friend of Kim Dec 12 '11 at 18:47
add comment

3 Answers

up vote 3 down vote accepted

$$\eqalign{&2x -{x+1\over 2}+{x+3\over 3 }={7\over 3}\cr &\iff12x \color{red}{- 3}(x+1) +{2 (x+3)}={14}\cr &\iff12x-3x\color{red}{-3}+2x+6 ={14}\cr &\iff 11x =11\cr &\iff x=1 } $$

You most likely forgot to "distribute the negative" (since you said you obtained $11x=5$).


To see what's going on there: we are using the rule that subtraction of a quantity is the same adding $(-1)$ times the quantity.

$$\eqalign{12x -3(x+1)&=12x +(-1)\cdot3 (x+1) \cr &=12x +(-3)(x+1)\cr &=12x+(-3)x+(-3)\cdot1\cr&=12x-3x-3.}$$

Of course, once you're accustomed to it, you just "distribute the negative sign".

share|improve this answer
add comment

$$\begin{align*} && 2x-\frac{x+1}{2}+\frac{x+3}{3} &= \frac{7}{3} & \cdot 6 \\ &\Leftrightarrow& 12x - 3x - 3 + 2x +6 &= 14 & \text{rearrange} \\ &\Leftrightarrow& 11x&=11 \end{align*}$$

share|improve this answer
    
Thanks, but 12x-3x, then you wrote -3, why isn't it +3? it says x+1 and not -1. Hopefully this is where I left of. Edit: Is x+1 one term? So it's like -(x+1) = -x-1 to remove the brackets? –  Friend of Kim Dec 12 '11 at 18:43
add comment

Multiply by $6$ to clear fractions:

$12x - 3(x +1) +2(x +3) = 14$

Eventually you'll get

$11x = 11$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.